Sociodemographic profile and neurofunctional evaluation of women in the pos-release of leprosy (Research, Society and Development, 2021)
Objective: To evaluate the simplified neurofunctional situation in post-discharge women from leprosy in a city in Alagoas, considering that these changes can affect the daily lives of women and their family and social relationships. Method: Cross-sectional and descriptive study, in which a neurofunctional assessment was carried out in post-discharge women from leprosy and socio-demographic aspects. Relative and absolute frequencies were calculated using Excel. Results: Regarding socio-demographic aspects, most were housewives, mixed race, elementary school I and self-reported receiving up to 1 and a half minimum wage. In the neurofunctional evaluation, a higher occurrence of sensory alterations was found in comparison with the motor ones, as well as the absence of physical deformities. Conclusion: It was found that the service was weak in following up post-discharge women due to a cure for leprosy, in view of the psychological, physical and social repercussions that the disease can cause to a greater extent in females. In the post-discharge period, prevention and management of residual disabilities are still a challenge, as the patients have already completed the treatment.